Kajian kesan kerosakan tompokan oleh mikrojet - Ayof, Mohamad Nizam (2001)
A hydrodynamic phenomenon that normally receives mere attention is cavitation. The presence of cavitation bubble in a system that involves fluid flowing causes a lot of trouble. Damage, erosion and noise is some of the effects of these phenomena. Although, a lot of efforts had been put forward to determine the cause of damage but yet, until now, no solution had been discovered. To throw some light, this work was carried out in order to contribute one possible solution to the problem. This is performed by concentrating only one aspect of damage mechanism that is microjet. Parallel to this objective, we used a fundamental approach by using a single bubble. A Q-switched Nd:YAG laser was employed as a source of a single cavitation bubble near a solid boundary. Metallurgical and soft surface technique was conducted to analyze the damage obtained due to the accumulation of single bubble exposure. The damage mechanism was identified in conjunction with a high-speed photographic technique. The observation results were utilized to determine the impact pressure and velocity of the microjet. The maximum velocity was found as 169.5 ms-' associated with water hammer pressure of 254.250 MPa. Such impressive pressure is enough to damage even hard boundary. This is also consolidating by magnifying the result of cavitation damage. Nevertheless the whole damage pattern is in an annular form, but on top of the ring is fully comprised of individual pits. The average area and diameter are found to be 0.0052 mm2 and 0.08 15 mrn respectively. No doubt that no other mechanism poses such smaller size except microjet. The measurement and observation results confirmed that microjet is the dominant mechanism of damage.